Attacking poverty in Bolivia - Past evidence and future prospects: Lessons from a CGE analysis - Rainer Thiele; Manfred Wiebelt (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2003)
This paper reviews Bolivia's economic and social development over the period 1985-99, and investigates the country's future prospects for pro-poor growth using a Computable General Equilibrium (CGE) model. It turns out that past economic growth cannot be called pro-poor. Model simulations show that under optimistic assumptions the growth and poverty goals envisaged in the Bolivian poverty reduction strategy may be achieved, but that performance will fall short of expectations once external shocks are taken into account. The evolution of poverty is likely to remain uneven, with considerable improvements in urban areas and a high persistence in rural areas.
Keywords: 330; Entwicklung; Wirtschaftswachstum; Armut; Einkommensverteilung; Armutspolitik; Allgemeines Gleichgewicht; Bolivien